2006
DOI: 10.1103/physreva.74.032305
|View full text |Cite
|
Sign up to set email alerts
|

Optimal cloning of mixed Gaussian states

Abstract: We construct the optimal 1 to 2 cloning transformation for the family of displaced thermal equilibrium states of a harmonic oscillator, with a fixed and known temperature. The transformation is Gaussian and it is optimal with respect to the figure of merit based on the joint output state and norm distance. The proof of the result is based on the equivalence between the optimal cloning problem and that of optimal amplification of Gaussian states which is then reduced to an optimization problem for diagonal stat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…In [14,13] it is shown that the quantum version of the local asymptotic normality with the Le Cam type convergence holds for identically prepared qubits with the limit experiment being a family of displaced thermal equilibrium states. In [15], the problem of optimal cloning of mixed quantum Gaussian states is solved along lines similar to the solution of the classical problem of finding the deficiency between two Gaussian shift experiments.…”
Section: Example 22mentioning
confidence: 99%
“…In [14,13] it is shown that the quantum version of the local asymptotic normality with the Le Cam type convergence holds for identically prepared qubits with the limit experiment being a family of displaced thermal equilibrium states. In [15], the problem of optimal cloning of mixed quantum Gaussian states is solved along lines similar to the solution of the classical problem of finding the deficiency between two Gaussian shift experiments.…”
Section: Example 22mentioning
confidence: 99%
“…In other words, the output state is the same as the state of the 'amplified' mode c when b and a are prepared in states τ and respectively Φ. From this point we follow closely the arguments used in [25] which were originally devised for finding the optimal amplification channel for displaced thermal states. The candidate channels are labelled by diagonal matrices τ and we denote by p τ the probability distribution consisting of the elements of the output state p…”
Section: H(dζ) := |ζ ζ|Dζ/2πmentioning
confidence: 86%
“…Now, since Φ is invariant under phase rotations, Φ = exp(iθN )Φ exp(−iθN ), we can apply the covariance argument again [25] to conclude that we can restrict to channels which are covariant under phase rotation, which amounts to taking τ to be diagonal in the Fock basis. Since for diagonal states f (ξ) = f (|ξ|) we obtain the following Schrödinger version of (7) Tr…”
Section: H(dζ) := |ζ ζ|Dζ/2πmentioning
confidence: 99%
See 2 more Smart Citations